Learning by making – student-made models and creative projects for medical education: systematic review with qualitative synthesis - Tan Yong Yi; Panwar Shreyans; Ranganath Vallabhajosyula (BMC Medical Education)
Abstract Study Objective Student-centered learning and unconventional teaching modalities are gaining popularity in medical education. One notable approach involves engaging students in producing creative projects to complement the learning of preclinical topics. A systematic review was conducted to characterize the impact of creative project-based learning on metacognition and knowledge gains in medical students. Methods A systematic search was conducted using MEDLINE and Embase via Ovid, PubMed, CINAHL, Web of Science, Cochrane CENTRAL, and Scopus from January 1st, 1995, to July 6th, 2023. Studies using quantitative, qualitative, or mixed-methods approaches that explored the impact of creative project-based lessons on medical students' educational outcomes were included. Two investigators independently screened the titles and abstracts and extracted data from included articles. A narrative synthesis was conducted to summarize study designs and outcome measures. Content analysis was conducted to generate codes and themes. Study quality was assessed using the Mixed Methods Appraisal Tool in view of the range of study types employed. Results The review included 17 studies published between 2010 to 2022. These studies implemented various creative project interventions such as handicraft models, drawings, and concept maps covering multiple topics, including anatomy, histopathology, and fundamental sciences. The identified themes of Enhanced Learning, Collaborative Learning, and Deep Learning led to further themes of Student Engagement, Student Disengagement, and Faculty Engagement. Collaborative learning involves students working in teams and benefitting from effective mentorship. Creative projects facilitated deep learning objectives via interdisciplinary learning and promoted new ways of perceiving concepts. Learning was enhanced through increased interactivity, high conceptual fidelity and improved knowledge retention. Conclusion Creative projects undertaken by medical students exhibit attributes that facilitate the acquisition of collaborative and deep learning objectives through self-directed learning, cognitive load modulation, and metacognitive behaviours. Faculty mentorship and group learning amongst peers facilitate these processes, although challenges such as high task demands, cognitive and emotional intensiveness, and mismatch with students; professional identities remain. Overall, students and faculty received these interventions well, thus, warranting further exploration for uses in medical curricula. Trial registration Not applicable as this study is a systematic review.